Development of pituitary dysfunction and destructive thyroiditis is associated with better survival in non-small cell lung cancer patients treated with programmed cell death-1 inhibitors: a prospective study with immortal time bias correction - Suzuki, Koji; Kobayashi, Tomoko; Izuchi, Tetsushi; Otake, Koki; Ando, Masahiko; Handa, Tomoko; Miyata, Takashi; Sugiyama, Mariko; Onoue, Takeshi; Hagiwara, Daisuke; Suga, Hidetaka; Banno, Ryoichi; et al. (Frontiers in Endocrinology, 2024)
Abstract Background: Immune-related adverse events (irAEs) are reported to be associated with better overall survival (OS) in non-small cell lung cancer (NSCLC) patients treated with immune checkpoint inhibitors. However, there may be a bias in that patients who develop irAEs must survive long enough to experience the irAEs, and no prospective studies adjusting for immortal time bias (ITB) have examined the relationship between OS and pituitary dysfunction or the two different types of thyroid dysfunction: destructive thyroiditis and hypothyroidism without prior thyrotoxicosis (isolated hypothyroidism). Methods: Patients with NSCLC who received nivolumab or pembrolizumab at Nagoya University Hospital between November 2, 2015 and February 1, 2023 were enrolled. Endocrine irAEs were prospectively assessed during scheduled evaluations of hormone levels. The association between irAE development and survival when considering ITB was examined by time-dependent Cox regression analysis. Results: Of the 194 patients included, 11 (5.7%), 10 (5.2%), and 5 (2.6%) developed pituitary dysfunction, destructive thyroiditis, and isolated hypothyroidism, respectively. The development of pituitary dysfunction (HR 0.36, 95% CI 0.13–0.98, p = 0.045) and destructive thyroiditis (HR 0.31, 95% CI 0.10–0.97, p = 0.044), but not isolated hypothyroidism (HR 1.15, 95% CI 0.42–3.20, p = 0.786), was significantly associated with longer OS. Conclusion: NSCLC patients developing pituitary dysfunction and destructive thyroiditis showed better OS even after adjusting for ITB, suggesting that these irAEs indicate a better prognosis.